Inflammation- and angiogenesis-related biomarkers are correlated with cancer-related fatigue in colorectal cancer patients: results from the ColoCare Study - Himbert, Caroline; Ose, Jennifer; Lin, Tengda; Warby, Christy A.; Gigić, Biljana; Steindorf, Karen; Schrotz-King, Petra; Abbenhardt-Martin, Clare; Zielske, Lin; Böhm, Jürgen; Ulrich, Cornelia (European journal of cancer care, 2019)
Cancer-related fatigue is one of the most common side effects of colorectal cancer treatment and is affected by biomedical factors. We investigated the association of inflammation- and angiogenesis-related biomarkers with cancer-related fatigue. Pre-surgery (baseline) serum samples were obtained from n = 236 newly diagnosed colorectal cancer patients. Meso Scale Discovery assays were performed to measure levels of biomarkers for inflammation and angiogenesis (CRP, SAA, IL-6, IL-8, MCP-1, sICAM-1, sVCAM-1, TNFα, VEGFA and VEGFD). Cancer-related fatigue was assessed with the EORTC QLQ-30 questionnaire at baseline and 6 and 12 months post-surgery. We tested associations using Spearman's partial correlations and logistic regression analyses, adjusting for age, sex and body mass index. sICAM-1 and VEGFD showed a significant positive correlation with cancer-related fatigue at baseline and 6-, and 12-month follow-up (sICAM-1: r = 0.19, p = 0.010; r = 0.24, p = 0.004; r = 0.25, p = 0.006; VEGFD: r = 0.20, p = 0.006; r = 0.15, p = 0.06; r = 0.23, p = 0.01 respectively). Biomarkers of inflammation and angiogenesis measured prior to surgery are associated with cancer-related fatigue in colorectal cancer patients throughout various time points. Our results suggest the involvement of overexpressed sICAM-1 and VEGFD in the development of fatigue.
Gesehen am 05.12.2019